Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/prs.0b013e31827c6d90
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Antibiotic Prophylaxis for Implant-Based Breast Reconstruction with Acellular Dermal Matrix

Abstract: This study demonstrates significant differences in the rate of infection between the groups of patients undergoing the first stage of two-stage implant-based breast reconstruction who received postoperative antibiotic prophylaxis and the group that received only perioperative antibiotics. This study suggests that the optimal duration of postoperative antibiotic prophylaxis is at least 48 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 21 publications
0
44
0
Order By: Relevance
“…Until removal of all drains over the course of 2 weeks, patients received postoperative antibiotics. 19,20 Tissue expansion was performed starting on the third postoperative week, and a typical fill volume was 30 to 60 ml. However, one limitation of the study is that we did not formally determine whether all aspects of postoperative practice were held constant.…”
Section: Study Populationmentioning
confidence: 99%
“…Until removal of all drains over the course of 2 weeks, patients received postoperative antibiotics. 19,20 Tissue expansion was performed starting on the third postoperative week, and a typical fill volume was 30 to 60 ml. However, one limitation of the study is that we did not formally determine whether all aspects of postoperative practice were held constant.…”
Section: Study Populationmentioning
confidence: 99%
“…This non-inferiority study which included 112 patients, demonstrated no significant difference in infection rates between the treatment groups (19.4% vs 22.0%). These results conflicted with earlier observational studies which suggest significant benefits with extended antibiotics in ADM-assisted reconstruction [26]. More research is needed and well-designed multicentre prospective studies and ideally RCTs are required to establish best practice.…”
Section: Discussionmentioning
confidence: 70%
“…2427 The Surgical Care Improvement Project (SCIP) has dictated many of the current protocols and recommended minimizing postoperative antibiotics to 24 hours. Although uniform consensus with preoperative antibiotics has been achieved, there is controversy regarding postoperative antibiotic administration.…”
Section: Irrigation Antibiotic and Drain Protocolsmentioning
confidence: 99%
“…Avashia et al 24 demonstrated infection rates of 31.6% when antibiotic delivery was limited to <24 hours postoperatively, 7.9% with 48 hours of antibiotics, and 3.2% with >48 hours of antibiotics. Clayton et al 26 demonstrated a 2-fold increase in surgical site infection (34.3% vs 18.1%, P =0.004) and a 4-fold increase in reoperation (16.4% vs 4.3%, P = 0.002) when SCIP measures were followed compared with when they were not.…”
Section: Irrigation Antibiotic and Drain Protocolsmentioning
confidence: 99%